Poster: All-Electric Ground Operations for More Electric Aircraft - Deja, Jakub; Dayyani, Iman; Skote, Martin (Cranfield University, 2022)
Raising awareness about environmental issues shifts the aerospace industry towards electrification and the corresponding solutions are already present from the airport perspective. Commercial aircraft are the missing links in claiming the all-electric ground operations. They rely on fossil fuels without any electric alternative due to the technological inability to store large amounts of energy while maintaining low weight of batteries. The possible mitigation is to utilize the available electrical energy with high efficiency. This paper demonstrates the landing gear drive system for a narrowbody airplane which has the sustainable and economic grounds to replace all onboard engines during ground operations. The novel concept of kinetic energy recovery during landing is brought together with the developments from recent publications. This combination is modelled and simulated in MATLAB/Simulink and leads to the kinematic results which are based on the authentic taxiing data. The kinematics are then used to estimate the overall on-ground power and energy demand of a more electric aircraft. The impact is maximized with the components scaled according to present and future performance metrics and two-stage gear ratio optimization. The net fuel advantage is demonstrated for different ground operation modes, taxi times and flight path lengths.
Keywords: more electric aircraft'; 'Hybrid Electric Vehicle'; 'Taxiing'; 'ground operations'; 'Kinetic Energy Recovery'